1998
DOI: 10.1097/00005176-199808000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Total and Segmental Colonic Transit Time with Radio-Opaque Markers in Adolescents with Functional Constipation

Abstract: The measurement of total and segmental colonic transit times is a simple method that allows one to distinguish constipation due to colonic dysfunction (right colon and left colon) from constipation due to distal obstruction (rectosigmoid).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 34 publications
2
65
0
3
Order By: Relevance
“…Compared with abdominal radiography, the accuracy of CTT was significantly better in this study population (AUC, 0.68; 95% CI, 0.58-0.80). 25 A 1-year follow-up study of children treated with laxatives or biofeedback showed results in favor of the discriminative ability of CTT. 37 In this study, children with a total CTT >100 hours had fewer treatment successes after 12 months than children with a shorter total CTT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with abdominal radiography, the accuracy of CTT was significantly better in this study population (AUC, 0.68; 95% CI, 0.58-0.80). 25 A 1-year follow-up study of children treated with laxatives or biofeedback showed results in favor of the discriminative ability of CTT. 37 In this study, children with a total CTT >100 hours had fewer treatment successes after 12 months than children with a shorter total CTT.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 All studies except one 24 were performed in referred children. The 6 included studies were heterogeneous for study design, the definition of constipation, and the methods used to evaluate the abdominal radiography (Table II).…”
Section: Abdominal Radiographymentioning
confidence: 99%
See 2 more Smart Citations
“…Entretanto, estudo recente evidenciou que algumas crianças com constipação crônica podem apresentar o padrão de retardo global de trânsito no cólon 36 . Outro estudo, realizado no Brasil, envolvendo adolescentes com e sem constipação crônica, constatou que foi o aumento do tempo de trânsito no cólon direito e esquerdo que mais contribuiu para o aumento do tempo de trânsito colônico total observado em adolescentes com constipação 37 .…”
Section: Fisiopatologia E Etiopatogeniaunclassified